The Orchidaceae of Primitiae Florae Essequeboensis (1818) - Ossenbach, Carlos (Universidad de Costa Rica, 2018)
The German botanist and Professor at the University of Göttingen, Georg Friedrich Wilhelm Meyer (1782–1856), studied the plants collected in the Dutch colony of Essequibo by Ernst Carl Rodschied and those kept in the herbarium of Professor Franz Karl Mertens, which he had received from a Dutch colonist during the early 1800s. On that basis, he published in 1818 his work Primitiae Florae Essequeboensis, describing 344 species of plants. Among them there are five species of orchids, two of which were new to science.